Effectiveness of Structural Legal Assistance in Land Disputes Involving Former Ptpn Ii Land Use Rights: Case Study Medan–Deli Serdang 2024–2025 - Rizki Nanda Fauzi Harahap; Rahul Ardian Fikri; Syahranuddin Syahranuddin (Journal Evidence Of Law, 2026)
This study aims to analyze the effectiveness of Structural Legal Aid (BHS) in resolving disputes over former PTPN II concession land in the Medan–Deli Serdang area in 2024–2025. These disputes involve communities affected by evictions, with plantation companies as the parties seeking land execution. SLL focuses on more equitable policy changes and community empowerment through legal assistance and policy advocacy. This study uses a legal-empirical approach with a case study design. Data were collected through in-depth interviews, field observations, and document analysis. The results show that SLL is effective in delaying evictions and increasing the legal capacity of the community, with 70% of residents feeling the benefits of the legal assistance provided. Factors supporting the effectiveness of BHS include active community participation and the involvement of supporting institutions, while obstacles include a lack of coordination between relevant agencies and limited resources. This study provides policy recommendations to improve fairer agrarian governance, which can reduce conflict and increase the protection of community rights in disputes over ex-HGU land.